Educational Governance in China - Yang, Ming (Springer Singapore, 2018)
This book presents a comprehensive and cutting-edge overview of the educational governance reform trajectory and the latest issues in China, addressing several important topics such as administration, internal management, provision, enrollment, employment, financing, examinations, evaluation and quality assurance. In addition, this important and timely book discusses the educational system at all levels, from primary and secondary schools to colleges and universities, and each chapter ends with a discussion of the status quo, problems facing China and coping strategies for further reform. The past 68 years (1949-2016) have seen a sea change in social, economic, cultural, political and educational fields. Systematically describing the educational landscape in China, the book also reveals how the massive changes in China have shaped education, and how education has responded to the new demands placed on it. Offering essential insights into educational reform in China, the book represents a valuable resource, especially for researchers and graduate students in the field of education.